The effect of the demographic factors of micro-entrepreneur on financial literacy: case of Amanah Ikthiar Malaysia (AIM) - Abdul Razak, Dzuljastri; Hamdan, Hamdino; Uddin, Md Nazim (International Journal of Business, Economics and Law (IJBEL), 2020)
Financial literacy is very important in the success of any business venture. Amanah Ikhtiar Malaysia (AIM) formed in 1987 is the largest microfinance institutions that assist in the poverty eradication for Micro Small and Medium Enterprises (MSMEs) in Malaysia. The purpose of this study is to investigate whether demographic factors such as gender, age, marital status and education have an effect the financial literacy on micro-entrepreneurs. AIM micro-entrepreneur can be an engine for the financial growth and development of economy in Malaysia. However, we need to identify demographic factors on financial knowledge, financial socialisation agents, financial attitude, financial skills and accounting practice so that appropriation actions can be taken to ensure the success of their business. This research is conducted using a survey method whereby 312 selfadministered questionnaires were collected from AIM micro-entrepreneur throughout Malaysia. The analysis adopts a quantitative research approach with a descriptive research design. A random sampling technique was used for this study. Data are analysed using the Statistical Package for Social sciences (SPSS). The results showed that entrepreneurial businesses fail because they have got unsatisfactorily low financial literacy. Therefore, recommendations include awareness and usage of authorities support programmes to improve the financial literacy of micro-entrepreneurs. MSMEs are also motivated to enrol for a certificate in financial literacy to improve and enhance their financial management to run their businesses effectively. This study would guide policies and guidelines for the adoption of by the regulators and government.